Analysis of the Beijing Opera facial masks based on the Chinese traditional culture - Shu, Li Xiao; Mohd Yusof, Mohd Johari (Universiti Pendidikan Sultan Idris, 2020)
This paper introduces the types and features of Beijing Opera facial masks, as well as the limitations of the “essence determines appearance” thinking pattern of Chinese traditional culture. The Chinese Beijing Opera facial masks are one of the symbols of Chinese traditional culture, while carrying forward the essence, it also disseminates the dross that the good people look good and the bad people look ugly. It is a wrong way to pursue too much of the people’s appearance and even simply use it as a yardstick to judge good or bad. This method can provide misunderstanding to many good people who are not good-looking in real life. Applying the classification of the opera facial masks in real life will hurt many good people with the ordinary appearance and will also be deceived by the bad people with good-looking appearance. Obviously, it is very important to break the limitations of the traditional Chinese culture and eliminate its dross by means of correctly understanding and applying the Beijing Opera facial masks, and overcoming the value judgment that the good people look good and the bad people look ugly.